Sustainable Observations of the AMOC: Methodology and Technology. (8th January 2020) - McCarthy, G. D.; Brown, P. J.; Flagg, C. N.; Goni, G.; Houpert, L.; Hughes, C. W.; Hummels, R.; Inall, M.; Jochumsen, K.; Larsen, K. M. H.; Lherminier, P.; Meinen, C. S.; et al.
Key Points: The AMOC is a system of ocean currents that move heat and carbon around the planet and is predicted to decline in the future The AMOC has been directly measured since the 2000s, but we now have observation systems in place that can verify a future decline We look at how these systems might develop in the future and consider how they might fit in an optimized Atlantic observing system Abstract: The Atlantic Meridional Overturning Circulation (AMOC) is a key mechanism of heat, freshwater, and carbon redistribution in the climate system. The precept that the AMOC has changed abruptly in the past, notably during and at the end of the last ice age, and that it is "very likely" to weaken in the coming century due to anthropogenic climate change is a key motivation for sustained observations of the AMOC. This paper reviews the methodology and technology used to observe the AMOC and assesses these ideas and systems for accuracy, shortcomings, potential improvements, and sustainability. We review hydrographic techniques and look at how these traditional techniques can meet modern requirements. Transport mooring arrays (TMAs) provide the "gold standard" for sustained AMOC observing, utilizing dynamic height, current meter, and other instrumentation and techniques to produce continuous observations of the AMOC. We consider the principle of these systems and how they can be sustained and improved into the future. Techniques utilizing indirect measurements, such as satellite altimetry, coupled with in situ measurements, such as the Argo float array, are also discussed. Existing technologies that perhaps have not been fully exploited for estimating AMOC are reviewed and considered for this purpose. Technology is constantly evolving, and we look to the future of technology and how it can be deployed for sustained and expanded AMOC measurements. Finally, all of these methodologies and technologies are considered with a view to a sustained and sustainable future for AMOC observation. Plain Language Summary: The Atlantic Meridional Overturning Circulation (AMOC) is a system of ocean currents (sometimes known as the Gulf Stream System or the Great Ocean Conveyor Belt) that is important because of how it moves heat and carbon around the planet. Due to human‐induced climate change, the AMOC is predicted to weaken substantially, with adverse impacts for regions dependent on the supply of warmth from the AMOC, including northwest Europe. Surprisingly, given its importance, the AMOC has only been directly measured for the last decade or so. We now have observation systems in place that can verify a future decline in the AMOC, if it happens. In this paper we review these observation systems in terms of the technology and methodology used. We look at how these systems might develop in the future, including covering any gaps that might exist, and consider how they might fit in an integrated and optimized Atlantic observing system.